Capital Structure, Liquidity, and Firm Value: The Mediating Role of Profitability in Food and Beverage Firms - Sri Agustina; Nursia Nursia; Novita Novita (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study examines the effects of capital structure and liquidity on firm value, with profitability as a mediating variable, in food and beverage companies listed on the Indonesia Stock Exchange during 2020–2024. Research Method: This study employed a quantitative approach using panel data analysis. Secondary data from 44 food and beverage companies listed on the Indonesia Stock Exchange during 2020–2024 were selected through purposive sampling. Firm value (Tobin’s Q), capital structure (DER), liquidity (CR), and profitability (ROA) were analyzed using panel regression and the Sobel test with EViews 12. Results and Discussion: Capital structure, liquidity, and profitability have no significant effect on firm value. Profitability also fails to mediate the relationships between capital structure, liquidity, and firm value, indicating that other factors may better explain firm value. Implications: The findings suggest that other factors may better explain firm value. Future research should examine additional determinants across different sectors and periods. Originality: This study contributes updated evidence by examining profitability as a mediating variable in food and beverage companies listed on the Indonesia Stock Exchange during 2020–2024.